Aplikasi Perpustakaan di SMA YAPEMRI Depok Timur Berbasis Web - Doni Dwi Saputro; NM Faizah; Winton Ginting (Design Journal, 2023)
The library is part of a separate building or structure that contains a collection of books, which are arranged and arranged in such a way that it is easy to find and use them at any time when needed by readers. Along with the development of the times, many libraries have abandoned the manual system and switched to a digital system. However, the Yapemri library still uses a manual system from borrowing to freezing, so it is not uncommon for opening files to be lost. This causes losses to the library because many loan reports are often lost. Therefore, by utilizing technology the research team developed the Yapemri library application so that the library no longer uses a manual system. The Yapemri Library application was created using the PHP programming language and MySQL as the Xampp database as a web server. This application has gone through two stages of testing, namely user testing and black-box testing. The test results with black-box show that all the features in the application run well. The results of the responses from users stated that they were quite good for this application. Thus, the authors can conclude that the website-based Yapemri library application is successful.